Integrating ESG in Corporate Restructuring: Comparative Legal Frameworks of Indonesia and Singapore - Sheilla Bintang Aerielisty (Nusantara: Journal of Law and Islamic Law, 2026)
This article comparatively analyzes the integration of Environmental, Social, and Governance (ESG) standards within corporate restructuring frameworks in Indonesia and Singapore. Driven by the global transition towards stakeholder capitalism, this study investigates how structural disparities in positive law and fiduciary duty doctrines dictate legal due diligence in mergers and acquisitions. Utilizing a comparative doctrinal methodology, the analysis applies stakeholder and legitimacy theories to evaluate the Indonesian Company Law and antitrust regulations against Singapore's mandatory reporting regime. The findings demonstrate that Indonesia's fragmented regulatory architecture and purely quantitative merger control mechanisms facilitate impression management, exposing acquiring entities to severe extraterritorial liabilities. Conversely, Singapore effectively mitigates these risks through institutionalized compliance and dynamic judicial interpretation. The research concludes that amending Indonesia's corporate law to mandate ESG due diligence and instituting a preliminary green antitrust evaluation are imperative to prevent greenwashing and ensure legal certainty in sustainable transnational business consolidation and corporate transactions.